RARE EARTH ELEMENTS AS TRACERS OF GEOCHEMICAL EVOLUTION OF MANTLE MATTER (FROM A STUDY OF PERIDOTITE NODULES) - Ryabchikov I.D.; Kogarko L.N.; Kovalenko V.I.; Kolesov G.M.; Shubina N.A.; Ionov D.A. (My University, 1988)
The study of mantle xenoliths is the basis for identifying the mechanisms via which the earth has undergone irreversible differentiation. The Shavaryyn-Tsaram volcano (Mongolia), known for its abundance of large nodules of different compositions unaltered by secondary processes, is a very good site to conduct such a study. We report new analytical data on the trace and rock-forming elements in mantle xenoliths from that volcano. We wanted to determine the composition of the fluids whose flows in the mantle produced the geochemical evolution of its material. Our data on REE contents in mantle xenoliths from Mongolia indicate that even though these nodules belong to the spinel peridotite facies, they were formed by processes that have occurred out of much greater depths, under conditions at which garnet is stable. In all likelihood, the alkali-basalt igneous activity of Mongolia developed during large-scale ascending flows in subcrustal zones.